Trade Liberalization, Export and Import Growth: Evidence from Uganda - Kilimani, Nicholas; Sebaggala, Richard (Makerere University, 2009)
The study explores the impact of trade liberalization on export and import growth in Uganda. A number of developing countries have opened up their own economies to take full advantage of the resultant opportunities for economic development through trade. Proponents of trade liberalization envisage positive results emanating from the increased competition in the sector. For instance, liberalization aids competition in the market, by increasing the basket of goods and services with better quality and lower prices. However, trade liberalization in developing countries has been criticized for increasing import penetration on the pretext of opening up the sector to more competition. The reason is that trade policy reforms tend to have a more immediate effect on the imports than on the exports. This concern has motivated researchers to investigate whether or not the impact of trade liberalization has been greater on export growth than on import growth. This is because Uganda is one of the countries to have implemented significant economic reforms, including the liberalization of the trade regime, over the last two decades and a half. These reforms have been both external and domestic. Substantial progress has been made to reduce tariff and non-tariff barriers through the EAC. The study investigated the issue using macro and micro analysis of the Ugandan economy. The macro analysis was employed by estimating the export and import models estimated using Vector Error-Correction modeling (VECM) using time series macroeconomic data for the period 1981-2009. The results of the study suggest that trade liberalization has led more to growth in imports than exports. The macro study findings are in line with previous observations made by Morrissey, et al., (2003); Santos-Paulino (2003); Santos-Paulino & Thirlwall (2004) and Hye & Mashkoor (2010). With regard to the micro analysis several, issues under the trade sector were highlighted that could be linked to the macro evidence which were; larger growth in imports than exports. Such critical issues included the adverse effect of the dismantling of the marketing boards, the inadequacy of the trade sector infrastructure, the low value addition and limited research and dissemination of the ever-changing trends in international trade regarding the products on high demand, the standards required to access such markets as well as the absence of value chains in the tradeables sectors. These have served to inhibit export growth. These issues were manifested at a macro level analysis for instance in the weak significance of the coefficient of the foreign income as well in that of the reel exchange rate in the export growth model
Keywords: Trade Liberalization; Export; Import Growth; Evidence